PENDAMPINGAN BAGI PENGENTASAN KEMISKINAN NELAYAN MELALUI KONSELING KARIR DI PANTAI BARAT KOTA PADANG - Abd Rahman; Mellyarti Syarif; Afnibar Afnibar; Meri Susanti (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Most of the fishermen in the territory of Indonesia are in the poverty line. This cannot be denied because they are in the limitation of knowledge and mastery of technology so that it depends more on the facilities provided by nature. When a lot of their catch is faced with the situation of cheap sale of fish. This condition certainly needs to be addressed and become the concern of various parties including universities that carry out the duties of the triharma of PT through community service. This activity is the provision of insight, knowledge and skills to the fishing community, especially in processing fish into snacks that are of value for sale and increase the variety of people's nutritional intake. Assistance to fishermen is carried out in three stages of activities, which include: pre-activity activities, activities and monitoring. Increased work ethic of fishermen, motivation for entrepreneurship and skills in processing fish are carried out through training, with resource persons from career counseling experts, leaders of trade and industry services and fish processing experts.